DETERMINATION OF BUILDING INTENSITY IN MANADO CITYâS B ON B AREA BASED ON ROAD CAPACITY AND WATER SUPPLY - Ketzia Tulangow, Pingkan
Basically building intensity is an instrument to controlling the density of a location. Type of land use, land price, economic factors and capacity of infrastructure are needs to be considered to determine the building. Consideration about capacity of infrastructure is often not prioritized in determining building intensity. High building intensity will increase trip generation and trip attraction, which require an appropriate road capacity to support the existing trips. High intensity of the building also requires more supply of clean water. However, the capacity of roads and clean water are limited, so they can only provide a certain number of needs. The B on B area of Manado City is the commercial area for Manado that located on the coast area and some parts of this area are on reclaimed land. This condition makes this area can’t increase road capacity by road widening because of the limited space and brackish groundwater causes the main water source is from PT. Air Manado. Manado also does not have a legal regulation that concerning determination of building intensity. Necessary to determine the building intensity in Manado City’s B on B area based on road capacity and water supply. This research is a prescriptive study with a supply demand approach and quantitative method is the research methods that used. This study formulates a model for calculating the maximum building intensity with road capacity and clean water supply as the limit. The model is compiled based on the relation between building intensity and road capacity and water supply. The maximum volume that can be accommodated by the road is compared to the number of generated and attracted movements per unit for each land use to obtain the maximum building intensity based on road capacity. Based on the provision of water, it will compare the volume of water availability with the standard nondomestic water needs to obtain the maximum building intensity. Based on the analysis, several findings were obtained in this study. The service level of Jalan Piere Tendean is in category F where the VCR is 0.64 and the vehicle speed is 13.8 km / hour. The volume of water supplied to Manado City B on B based on the volume of water production is 4,466,372.5 liters / day. The calculation of building intensity considers the land use according to the Manadoiv City spatial plan and the proportion of existing land uses. The result that used is the building intensity with land use according to the Manado City spatial plan, because it is considered more relevant to be used as a reference. Based on the calculation of the maximum floor area Ratio (FAR) based on the road capacity in segment 1 0.96 segment 2 0.98, segment 3 0.92 and segment 4 1.25. Based on water supply the maximum FAR in segment 1 8.44, segment 2 7.15 segment 3 3.66 and segment 4 6.75. Based on the results, FAR that is determined to be the maximum FAR is the FAR based on the road capacity because it has a smaller number than the intensity of the building based on the provision of water. The determined maximum FAR cannot be applied because the existing FAR is over the Maximum FAR. The existing FAR in segment 1 0.95, segment 2.16, segment 3 1.28 and segment 4 1.76. Recommendation based on the results are Manado City’s Government needs to optimize road capacity by diversifying lanes and providing parking spaces to avoid on-street parking, reducing vehicle volume by providing mass transportation and the government needs to make a guideline to determining building intensity in Manado City. Optimize road capacity and reduce vehicle volume so that road capacity can support activities with the current intensity of buildings